Membrane‐Mediated Self‐Organization of Rod‐Like DNA Origami on Supported Lipid Bilayers - Alena Khmelinskaia; Henri G. Franquelim; Renukka Yaadav; Eugene P. Petrov; Petra Schwille (Advanced Materials Interfaces, 2021)
Abstract Organization of elongated particles into ordered phases on 2D surfaces and interfaces has been extensively studied during the last decades both theoretically and experimentally. For mutually repulsive particles on solid nondeformable substrates, the process is controlled only by the aspect ratio and the surface density of the adsorbed particles. The local elastic response of soft substrates to particle adhesion can drastically change the collective behavior of adsorbed rod‐like particles resulting in their self‐organization via substrate‐mediated interparticle attraction. Here, high‐speed atomic force microscopy is used to study the organization of DNA origami particles on locally responsive supported lipid bilayers (SLBs) in comparison with that on nondeformable solid mica surfaces. At high surface coverage, the aspect ratio‐dependent anisotropic phases expected for densely packed particles are observed. At intermediate and low surface densities, however, a drastically different phenomenology is observed: surprisingly strong surface‐mediated interparticle attraction of DNA origami particles is found on SLBs resulting in their self‐organization compared to their purely repulsive interaction on a mica surface. The formation of organized aggregates of elongated DNA origami particles on SLBs is explained by exceptionally strong nanoparticle adhesion to the membrane that responds with a local deformation in spite of the presence of the solid support.